2006
DOI: 10.1002/pssc.200672126
|View full text |Cite
|
Sign up to set email alerts
|

Diabatic theory of the dynamical structural change triggered by injection of photoexcited states

Abstract: We study the coherent dynamics of the initial processes of structural change in strongly interacting electronphonon systems triggered by photoexcitation. We employ a model of localized electrons coupled with a single phonon mode, which is fully quantized in order to calculate the dynamics of consecutive switching of potential surfaces. We found that the interplay of the interaction between vibrational degrees of freedom and the Coulomb interaction between electrons is the key to understand the domain growth pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…They have mentioned that the dynamics of photoinduced domain growth is a key to understand the physics of the photoinduced cooperativity, and many experimental and theoretical studies have been performed to reveal the mechanism of these phenomena [2,3,5,6,7,4,8,9,10,11]. Above all, interdomain interaction and/or nonlinearity in the pattern formation process of photoinduced domains is important to understand their dynamical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have mentioned that the dynamics of photoinduced domain growth is a key to understand the physics of the photoinduced cooperativity, and many experimental and theoretical studies have been performed to reveal the mechanism of these phenomena [2,3,5,6,7,4,8,9,10,11]. Above all, interdomain interaction and/or nonlinearity in the pattern formation process of photoinduced domains is important to understand their dynamical properties.…”
mentioning
confidence: 99%
“…As for the theoretical study of these phenomena, we have proposed a model of molecular crystals to describe the initial nucleation processes of photoinduced domains [10,11]. We found that an initially excited molecule becomes a nucleus of a photoinduced domain, and that its growth dynamics is understood by the numerical solutions of the time-dependent Schrödinger equation.…”
mentioning
confidence: 99%
“…We have pointed out that the population of the excited electronic state | ↑ r is suitable for understanding the dynamics of the initial nucleation processes [10,11]. Thus, we show in Fig.…”
Section: Calculated Resultsmentioning
confidence: 78%
“…As we have shown in the previous papers [10,11], nonadiabaticity of electronic transitions is a key to understand the temporal behavior of the above-mentioned phenomena. Dynamics of nonadiabatic transitions has been studied since the pioneering works by Landau [12] and Zener [13], and the bifurcation rate of wavefunction was analytically obtained in general cases [14].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation